2011
DOI: 10.1142/s0192415x11008932
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Auricular Acupressure on Weight Reduction and Abdominal Obesity in Asian Young Adults: A Randomized Controlled Trial

Abstract: The current study was designed to test the efficacy of auricular acupressure on weight reduction and changes of waist circumference and waist-to-hip ratio. This study used a randomized design with one control group and one experimental group consisting of Asian young adults with a waist circumference ≥80 cm in the females and ≥90cm in the males. At completion of eight weeks of auricular therapy, the total sample size was 55 young adults who ranged in age from 18 to 20 years old. Each participant was treated we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 12 publications
0
39
0
Order By: Relevance
“…Details about acupuncture points used, retention time, frequency, and duration of acupuncture sessions were shown in Table 2 . In these research, 30 articles [ 26 – 30 , 32 , 34 38 , 41 – 59 ] reported the weight loss, while 25 articles reported the change in BMI. The details of mean, standard difference (SD), and sample size between different groups for eligible studies are summarized in Appendix 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Details about acupuncture points used, retention time, frequency, and duration of acupuncture sessions were shown in Table 2 . In these research, 30 articles [ 26 – 30 , 32 , 34 38 , 41 – 59 ] reported the weight loss, while 25 articles reported the change in BMI. The details of mean, standard difference (SD), and sample size between different groups for eligible studies are summarized in Appendix 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Stimulating a particular acupoint with acupressure can activate small myelinated nerve fibers that send impulses into the spinal cord, midbrain, pituitary, and hypothalamus26. AA, a treatment method derived from acupressure and ear acupuncture, is a safer, more effective, economic and simple approach362728293031. The practical advantages of AA include3233: (1) only minimal equipment is needed and any physicians or nurses can perform this treatment; (2) physicians as well as other health care providers who have rare or no experience in traditional Chinese medicine can learn this technique within a few hours and can use it whenever indicated; (3) it is almost a “no-cost” intervention; (4) AA is non-invasive and does not affect the integrity of the epidermis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that auricular acupuncture is a reasonable for treating patients who are overweight. [14][15][16][17] Auricular acupuncture points for treating obesity are: Shenmen, Spleen, Mouth, Stomach, Endocrine points, Small Intestine, Large Intestine, and Hunger. [17][18][19][20][21] There are also other acupoints used to treat obesity; however, not all of them were used in the current study because of the practical procedures required in the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Different kinds of methods-including auricular acupuncture, 21 auricular acupressure, 14-16 auricular electroacupuncture, 19 and transcutaneous electrical nerve stimulation 20 -have been used to treat obesity. The vaccaria line seed 18 and magnetic pearls 14,15 are used for auricular acupressure.…”
Section: Discussionmentioning
confidence: 99%